A Study of Subway Marketing 4P Strategy - Ganatra, Varsha; Utama, A.A. Gde Satia; Puran, Puran; Pandey, Rudresh; Qi, Liang Mei; Kee, Daisy Mui Hung; Ling, Irene Saw Ai; Sien, Lim Hooi; Tien, Tan Jia; Ramadhan, Hafizh Sasining; Sin, Liem Gai; Pandey, Madhu Ashok (Asia Pacific Journal of Management and Education (APJME), 2021)
The purpose of this study is to examine Subway marketing 4P strategy as the competition in the fast-food industry is extremely high. Subway is needed to keep on striving for better performances to build existing customer loyalty while attracting new customers. Therefore, we examine Subway marketing 4P (product, price, promotion, and place) to ensure that Subway can obtain a competitive advantage in the marketplace. The study used primary and secondary data methods to collect respondents’ perceptions of Subway performances. The findings indicated that marketing 4P strategies are the important prediction of the success of the company.